2005
DOI: 10.1186/1472-6963-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Time on wait lists for coronary bypass surgery in British Columbia, Canada, 1991 – 2000

Abstract: Background: In British Columbia, Canada, all necessary medical services are funded publicly. Concerned with growing wait lists in the mid-1990s, the provincial government started providing extra funding for coronary artery bypass grafting (CABG) operations annually. Although aimed at improving access, it is not known whether supplementary funding changed the time that patients spent on wait lists for CABG. We sought to determine whether the period of registration on wait lists had an effect on time to isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…This is particularly true for cardiac conditions, which are often amenable to evaluations based on index events such as cardiac catheterization and listing for surgery, which is captured by institutional, provincial and national datasets (1,7,8). We argue that, unfortunately, such wait time data underestimate the total wait time experienced by patients, which includes intervals in which the patient is waiting for different things and different people.…”
Section: Discussionmentioning
confidence: 96%
“…This is particularly true for cardiac conditions, which are often amenable to evaluations based on index events such as cardiac catheterization and listing for surgery, which is captured by institutional, provincial and national datasets (1,7,8). We argue that, unfortunately, such wait time data underestimate the total wait time experienced by patients, which includes intervals in which the patient is waiting for different things and different people.…”
Section: Discussionmentioning
confidence: 96%
“…This population-based patient registry contains demographic, clinical and treatment data, along with the dates of booking request for operating room time and procedures for all adult patients undergoing CABG in any of the four cardiac centers in the province [8]. To identify cardiac catheterization dates, hospital admission and discharge dates, and coexisting medical conditions, we used each patient’s provincial health number to deterministically link BCCR records to the Canadian Institute for Health Information (CIHI) Discharge Abstract Database (DAD) [11].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study of access to non-emergency CABG in British Columbia, Canada, between 1991 and 2000, we found that waiting times for the procedure shortened after 1998 when annual supplementary funding was granted to tertiary care hospitals that had been providing cardiac surgical care to adult residents of the province [8]. Between 1995–1996 and 1999–2000, there was a 12% increase in the total number of CABG operations and a decline in median waiting time from 15 to 10 weeks, although the change in waiting times was different across urgency groups.…”
Section: Introductionmentioning
confidence: 99%
“…Data were taken from a population-based registry set up to capture the time of registration for surgery, the time of surgery or removal from wait lists without surgery, for all patients accepted for coronary bypass surgery in the four tertiary hospitals delivering adult cardiac care to residents of BC [15]. Offices of all cardiac surgeons weekly provide information to the registry on registrations for surgery, operations performed, waitlist reconciliation (removals), and discharge summaries.…”
Section: Methodsmentioning
confidence: 99%
“…All cardiac surgeons in BC use a common guideline for prioritizing patients and assigning a target time for surgery based on angina symptoms, affected coronary anatomy, and left ventricular function impairment as described elsewhere [15]. Each patient was classified as urgent if the suggested time to surgery was three days, semi-urgent if the time was six weeks, and non-urgent if the time was 12 weeks.…”
Section: Methodsmentioning
confidence: 99%